CASE OF STREPTOCOCCOSIS IN PIGLET AT TUA VILLAGE, MARGA, TABANAN, BALI - Ni Kadek Puspa Dewi; I Gusti Ketut Suarjana; Ida Bagus Kade Suardana; Ida Bagus Oka Winaya; Ida Ayu Pasti Apsari (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Streptococcosis is a disease caused by streptococcal bacterial infection and can cause outbreaks in pig farms. This case study aims to discuss the pathological anatomy, histopathology, and laboratory test results to obtain a definitive diagnosis of the disease that attacks 7-day-old pigs from Tua Village, Marga, Tabanan. Data collection in the form of clinical signs, anamnesis, epidemiology, and laboratory tests to be further analyzed descriptively qualitatively. Clinical signs of pig cases are thin, weak, nervous symptoms (tremors, loss of balance, lying sideways, and cycling or rowing movements), white diarrhea, fatigue, and swelling of the leg joints. Epidemiological data show a morbidity of 8.13%, mortality of 3.25%, and a case fatality rate of 40%. Pathological anatomy examination was carried out through a necropsy procedure and found congestion of the brain, heart, and intestines, hemorrhage in the lungs, kidneys, stomach, and intestines, the spleen changed color to dark and swollen and the liver was swollen and uneven in color. Histopathological examination began with the preparation of histological preparations using Hematoxylin-Eosin (HE) staining, measurements were made by observing changes descriptively using a binocular light microscope with a magnification of 100x-1000x. The results of histopathological examination showed that the brain had meningoencephalitis hemorrhagica, lungs bronchopneumonia hemorrhagica, heart myocarditis, liver hepatitis, spleen splenitis hemorrhagica, kidney glomerulonephritis hemorrhagica et necrotican, stomach Gastritis hemorrhagica et necrotican, and intestine enteritis hemorrhagica et necrotican. Examination of histopathological preparations found inflammation dominated by neutrophil cells and macrophage cells. Bacteriological examination confirmed the presence of Streptococcus sp. bacterial infection in the brain, lungs, liver, and heart organs. Based on anamnesis, clinical signs, epidemiology, examination of anatomical and histopathological pathological changes, and bacteriological examination, it can be concluded that the pigs were infected with Streptococcosis due to Streptococcus suis bacteria. In pig farming management, optimal biosecurity and sanitation must be implemented to minimize the risk of contamination by disease agents.